Meibomian gland alteration in patients with systemic lupus erythematosus. (April 2022) - Li, Yixuan; Ou, Shangkun; Lin, Sijie; Qian, Hongyan; Zhao, Zhongyang; Zhang, Mengqin; Li, Siyang; Liu, Yuan; Shi, Guixiu
Purpose: To investigate meibomian gland (MG) alteration in patients with systemic lupus erythematosus (SLE). Methods: This study included 23 SLE patients evaluated with Systemic Lupus Erythematosus Disease Activity Index (SLEDAI) and 21 healthy controls (HCs). All the subjects were evaluated with Ocular Surface Disease Index (OSDI) questionnaire, and the eyes were performed examinations of tear meniscus height (TMH), non-invasive keratographic tear film break-up time (NIKBUT), Schirmer I Test, MG eyelid score, meibography score, and in vivo confocal microscopy (IVCM) on the meibomian gland. Results: There was no significant difference between the SLE patients and the HCs in the TMH, NIKBUT, and Schirmer I Test. However, the SLE patients had higher MG eyelid scores and meibography scores on both upper eyelid and lower eyelid than the HCs. Through meibography observation, 34.8% of the SLE patients presented MG deficiency in Grade 3, whereas that of all the HCs were less than Grade 3. The SLE patients were found to have significant MG atrophy and vascular enrichment around the meibomian glands (MGs). The SLE patients were also found to have excessive inflammatory cell infiltration around the MGs, especially the typical lymph node-like foci of inflammatory cell infiltration. Conclusions: MG alteration can be found in the SLE patients. Examinations of the MGs can help diagnose or infer ocular diseases at an early stage of SLE.